Procalcitonin and CRP as Biomarkers in Discrimination of Community-acquired Pneumonia and Exacerbation of COPD - Çolak, Ayfer (J Med Biochem, 2017)
BACKGROUND: Serum procalcitonin (PCT) and C-reactive protein (CRP) are markers of systemic inflammation and bacterial infection. We aimed to compare the usefulness of procalcitonin and CRP in patients with community-acquired pneumonia and exacerbations of chronic obstructive pulmonary disease (COPD). METHODS: A total of 116 consecutive patients were included in the study: 76 with chronic obstructive pulmonary disease in group 1, and 40 with pneumonia in group 2. RESULTS: Median serum CRP level was 44 mg/L in the COPD group and 132 mg/L in the pneumonia group. Median value of serum PCT was found to be 0.07 in the COPD group and 0.14 ng/mL in the pneumonia group. Serum PCT and CRP levels were significantly higher in the pneumonia group compared to the COPD group (p<0.001). The area under the ROC curve was 0.788 (CI: 0.704–0.872) for CRP and 0.699 (CI: 0.599–0.800) for procalcitonin to identify pneumonia. CONCLUSIONS: Procalcitonin and CRP levels were significantly higher in patients with community-acquired pneumonia presenting to the emergency department with indications for hospitalization than in patients with exacerbations of chronic obstructive pulmonary disease. Serum CRP and procalcitonin concentrations were strongly correlated. CRP might be a more valuable marker in these patients with lower respiratory tract infections.